An Unusual Cause of Dyspnea and Thoracic Pressure - Claire Chakkalakal; Rezo Jorbenadze; Meinrad Gawaz (Case Reports in Cardiology)
There is a high prevalence of hepatic cysts in the general population. Simple cysts are most of the times asymptomatic and are usually detected incidentally on ultrasonography, computed tomography, or magnetic resonance imaging. Symptoms may range from abdominal discomfort and pain, early satiety, dyspepsia, nausea, and vomiting to jaundice and portal hypertension due to obstruction of adjacent structures. Complications include spontaneous hemorrhage, infection, thrombosis, and atrophy of surrounding hepatic tissue. We present a unique case of a middle-aged patient with acute onset of dyspnea and thoracic pressure due to compression of the right ventricle by a large hepatic cyst.